Pathologic Basis of Disease/ Vinay Kumar - Kumar, Vinay (Estados Unidos de América : Elsevier Saunders, 2005)
We launch the seventh edition of Pathologic Basis of Disease whit mixed emotions, excitement and enthusiasm, as we enter the new millennium.
1. Cellular Adaptations 2. Thromboembolic Disease
Incluye Índice y Bibliografía
Col. Med
Keywords: 1. DISEASES OF IMMUNITY 2. NEOPLASIA 3. THE EYE